Utilization of Stenotrophomonas koreensis and Bacillus amyloliquefaciens for Improving Growth, Reducing Nitrogen Fertilization and Controlling Bipolaris sorokiniana in Wheat - Md. Motaher Hossain (Caraka Tani: Journal of Sustainable Agriculture, 2024)
Wheat (Triticum aestivum L.), a vital cereal, faces significant challenges from common root rot and spot blotch diseases caused by Bipolaris sorokiniana. This study aimed to explore the potential of plant growth promoting rhizobacteria (PGPR) to enhance wheat growth, reduce fertilizer input, and combat Bipolaris diseases. Two PGPR isolates, selected for their superior antagonistic properties, were identified as Stenotrophomonas koreensis RB11 and Bacillus amyloliquefaciens RB12. These PGPR strains displayed multiple plant growth promoting and biocontrol attributes, including phosphate solubilization, indole-3-acetic acid production, nitrogen fixation and antagonism against B. sorokiniana and other fungi. Wheat seed priming with the PGPR significantly improved germination, plant growth, nutrient content and biomass carbon accumulation in the rhizosphere soil. Importantly, the application of RB11 and RB12 allowed for a 25% and 50% reduction in nitrogen fertilizer usage, respectively, without compromising the yield. RB11 and RB12 also demonstrated potent inhibitory effects on B. sorokiniana conidial germination and significantly controlled common root rot and spot blotch in wheat, similar to those observed with the fungicide Protaf 250EC. Overall, this study underscores the multifaceted roles of S. koreensis RB11 and B. amyloliquefaciens RB12 in promoting wheat growth, reducing fertilizer inputs and effectively suppressing wheat pathogens. These findings contribute to the development of PGPR-based strategies for sustainable crop production and disease control.